PENGEMBANGAN LKS PENGAMATAN SUBPOKOK BAHASAN FILUM PLATYHELMINTHES, NEMATHELMINTHES, DAN ANNELIDA BERORIENTASI CONCEPT ATTAINMENT MODEL UNTUK KELAS X SMA - RAHMAWATI, AULIA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
Phylum Platyhelminthes, Nemathelminthes, and Annelida are studied in biology of grade X of senior high school, however the students get difficulty in distinguishing these three phyla because of similarities features. Therefore, direct observation of the objects are needed, hence the students can abtain concept by learning, not only memorizing. Observation can be done in learning using Concept Attainment Model (CAM). This study aimed to develop student observation-worksheet using CAM of subsubject Phylum Platyhelminthes, Nemathelminthes, and Annelida as well as describe theoretical feasibility of student observation-worksheets using CAM of subsubject Phylum Platyhelminthes, Nemathelminthes, and Annelida. The students worksheets were developed by using the Four-D models (define, design, develop, and disseminate), but the last stage was not done. Development was conducted during the January-September 2013. The theoretical feasibility of student worksheets was reviewed based on the result of the validation conducted by two lecturers and two biology teachers of senior high school on the feasibility of content, language, and presentation. Theoretical feasibility of the worksheets based on the results of expert validation was 3.75 (very good). Keywords: student observation-worksheets, Concept Attainment Model (CAM), Phylum Platyhelminthes, Nemathelminthes, Annelida, Senior High School grade X